Comparative Studies Of Bacteria And Fungi For The Removal Of Cu2+ Metal. - SHIPRA JHA; DR S.N DIKSHIT; DR G PANDEY (International Journal of Pharma and Bio Sciences, 2011)
The aim of this research work is to evaluate the efficiency of fungus and bacteria for the Cu2+ removal capacity .The bacteria and fungi was spread on Cu2+(50mg/l) and monitored after 24hr and fungus after 96hrs, purified & characterized based on morphological characteristics. Finally the result indicated that fungal strain A. lentulus absorb maximum amount of copper and have a high absorbing capacity.